Bioactivities and extraction optimization of crude polysaccharides from the fruits and leaves of Rubus chingii Hu. (5th October 2015) - Zhang, Tian-Tian; Lu, Chuan-Li; Jiang, Jian-Guo; Wang, Min; Wang, Dong-Mei; Zhu, Wei
Highlights: Leaf and fruit polysaccharides isolated from Rubus chingii Hu were compared. Antioxidant, antiinflammatory and anticancer bioactivities of L-Ps were better than F-Ps. Structural differences of F-Ps and L-Ps lead to their different bioactivities. Extraction process of L-Ps was optimized and the experimental yield was 9.57%. Abstract: Polysaccharides of Rubus chingii Hu fruit and leaf were extracted to compare their antioxidant, anti-inflammatory, and anticancer activities against breast cancer cells MCF-7 and liver cancer cells Bel-7402. Results showed that all the tested bioactivities of polysaccharides from leaf (L-Ps) were better than those of polysaccharides from fruit (F-Ps). Response surface methodology was then used to optimize the extraction conditions of polysaccharides from leaf. Additionally, polysaccharides from fruit and leaf were characterized and their contents of total sugars, proteins and uronic acid were compared. It was found that polysaccharides from fruit and leaf were similar in IR and UV absorption, but significantly different in contents of total sugars, protein and uronic acid. Their elution profiles of DEAE-Sepharose fast flow column were different too. The main peak of polysaccharides from fruit was eluted with 0.3 mol/l NaCl solution and the main peak of polysaccharides from leaf was eluted with deionized water. The differences between the two polysaccharides may be responsible for their differences in bioactivities. Further studies are required to explore their complete structural characteristics, structure-activity relationship and the mechanism of their activities.